Research on the transverse flexural static and fatigue performance of the joint between a corrugated steel web and a concrete roof. (1st June 2023) - Wang, Changyu; Yin, Shiping; Du, Jianhua; Shen, Hongyun
Abstract: To study the static and fatigue performance of the joint between the corrugated steel web and concrete roof under the action of a transverse bending moment, bending tests are conducted on four groups of 8 1:1 full-scale joint specimens, and the effect of different connector types is investigated. Moreover, the effect of prestress on the transverse flexural properties of twin perfobond shear connector (abbreviated as T-PBL) joint specimens is analysed. One specimen in each group is subjected to a static failure test to determine the ultimate bearing capacity and load‒deflection curve, and one specimen is subjected to a fatigue loading test to analyse the variation law of mechanical properties such as the ultimate bearing capacity, residual deflection and flexural stiffness during fatigue cyclic loading. The experimental results show that under the action of a transverse bending moment, the failure modes of joint specimens under static load and after fatigue static load are basically the same, but the failure modes of joint specimens with different types of connectors are different. The transverse flexural fatigue performance of the T-PBL joint and embedded connector joint is better than that of the stud connector joint. Specifically, after fatigue cyclic damage, the bearing capacity and stiffness of the T-PBL joint and embedded connector joint are not significantly degraded, while the bearing capacity and stiffness of the stud connector joint are greatly degraded. Applying transverse prestress can improve the transverse flexural static and fatigue performance of the T-PBL joint to a certain extent. Under the action of the fatigue load, the residual deflection of the joint will increase with increasing fatigue cycles. The development law of the residual deflection with the fatigue cycles is that the residual deflection increases rapidly in the initial stage and slowly in the later stage. Highlights: The transverse flexural performance of full-scale joint with 3 different connectors is explored. The transverse flexural fatigue performance of T-PBL, stud and embedded joint is compared. The fatigue cracks development law of the joints with 3 different connectors is explored. The influence of prestress on transverse flexural static and fatigue performance is explored.